Transcriptional characterization of Vibrio fischeri during colonization of juvenile Euprymna scolopes - Luke R. Thompson; Kiel Nikolakakis; Shu Pan; Jennifer Reed; Rob Knight; Edward G. Ruby (Environmental Microbiology, 2017)
Summary The marine bacterium Vibrio fischeri is the monospecific symbiont of the Hawaiian bobtail squid, Euprymna scolopes , and the establishment of this association involves a number of signaling pathways and transcriptional responses between both partners. We report here the first full RNA‐Seq dataset representing host‐associated V. fischeri cells from colonized juvenile E. scolopes , as well as comparative transcriptomes under both laboratory and simulated marine planktonic conditions. These data elucidate the broad transcriptional changes that these bacteria undergo during the early stages of symbiotic colonization. We report several previously undescribed and unexpected transcriptional responses within the early stages of this symbiosis, including gene expression patterns consistent with biochemical stresses inside the host, and metabolic patterns distinct from those reported in associations with adult animals. Integration of these transcriptional data with a recently developed metabolic model of V. fischeri provides us with a clearer picture of the metabolic state of symbionts within the juvenile host, including their possible carbon sources. Taken together, these results expand our understanding of the early stages of the squid–vibrio symbiosis, and more generally inform the transcriptional responses underlying the activities of marine microbes during host colonization.